Parental Knowledge of Children’s Developmental Milestones in Riyadh, Saudi Arabia - Abdulrahman S. Aldayel; Abdulaziz A. Aldayel; Ahmed M. Almutairi; Hamad A. Alhussain; Sultan A. Alwehaibi; Talal A. Almutairi (International Journal of Pediatrics)
Objective. Parental recognition of children’s developmental milestones has been correlated with more effective childcare strategies and overall better outcomes for children. However, the knowledge that parents have about children’s development remains uncertain which reflects serious concerns about children’s health in Saudi Arabia. Therefore, this study was undertaken to identify parents’ knowledge levels about children’s developmental milestones and the information sources they rely on for this knowledge. Study Design. We recruited 1471 parents aged ≥18 with at least one child under 14 and living in Riyadh to participate in an online survey between July of 2019 and January of 2020. Results. Most respondents showed a poor level of knowledge (80.0%) in all of four domains. However, mothers had more acceptable levels of knowledge (21.0%) than fathers (10.0%) (p≤0.01). There was a significant association between knowledge and age at first child’s birth; respondents who had their first child between 39 and 50 had the highest levels of knowledge (37.5%; p≤0.01). In the four domains of development, parents were found to have the most knowledge about physical development (52.3%), followed by cognitive development (21.6%), social development (21.5%), and emotional development (21.2%). Only a few parents (5%) claimed to always rely on their healthcare professionals for information. Conclusion. There is a lack of appropriate knowledge about developmental milestones among parents, which reflects serious concerns about children’s health in Saudi Arabia. Healthcare institutions and pediatricians currently play a minimal role in health education. Effective health education programs and strategies should be implemented to improve child development outcomes in the community.